Evaluating Models for Lithospheric Loss and Intraplate Volcanism Beneath the Central Appalachian Mountains. Issue 10 (11th October 2021) - Long, Maureen D.; Wagner, Lara S.; King, Scott D.; Evans, Rob L.; Mazza, Sarah E.; Byrnes, Joseph S.; Johnson, Elizabeth A.; Kirby, Eric; Bezada, Maximiliano J.; Gazel, Esteban; Miller, Scott R.; Aragon, John C.; et al.
Abstract: The eastern margin of North America has been shaped by a series of tectonic events including the Paleozoic Appalachian Orogeny and the breakup of Pangea during the Mesozoic. For the past ∼200 Ma, eastern North America has been a passive continental margin; however, there is evidence in the Central Appalachian Mountains for post‐rifting modification of lithospheric structure. This evidence includes two co‐located pulses of magmatism that post‐date the rifting event (at 152 and 47 Ma) along with low seismic velocities, high seismic attenuation, and high electrical conductivity in the upper mantle. Here, we synthesize and evaluate constraints on the lithospheric evolution of the Central Appalachian Mountains. These include tomographic imaging of seismic velocities, seismic and electrical conductivity imaging along the Mid‐Atlantic Geophysical Integrative Collaboration array, gravity and heat flow measurements, geochemical and petrological examination of Jurassic and Eocene magmatic rocks, and estimates of erosion rates from geomorphological data. We discuss and evaluate a set of possible mechanisms for lithospheric loss and intraplate volcanism beneath the region. Taken together, recent observations provide compelling evidence for lithospheric loss beneath the Central Appalachians; while they cannot uniquely identify the processes associated with this loss, they narrow the range of plausible models, with important implications for our understanding of intraplate volcanism and the evolution of continental lithosphere. Our preferred models invoke a combination of (perhaps episodic) lithospheric loss via Rayleigh‐Taylor instabilities and subsequent small‐scale mantle flow in combination with shear‐driven upwelling that maintains the region of thin lithosphere and causes partial melting in the asthenosphere. Plain Language Summary: For the past 200 million years, the east coast of North America has been situated in the middle of a tectonic plate. Contrary to the expectations for this setting, a region of the Central Appalachian Mountains centered near the boundary between the U.S. states of Virginia and West Virginia exhibits atypical properties. The unusual observations include volcanic activity in the geologic past far away from a plate boundary, elevated rates of erosion associated with high topography in the Central Appalachians, and anomalous structure in the upper mantle that has been detected using geophysical methods. This article describes, synthesizes, and compares a suite of observations that show that this part of the Central Appalachians is unusual compared to other so‐called passive continental margins. We discuss a range of different models that might describe how the lithosphere, or the rigid part of the crust and upper mantle that defines the tectonic plate, has evolved through time beneath our study region. We show that the lithosphere today is thin, and that past episodes of lithospheric loss involving a portion of dense lithosphere "dripping" into the mantle under the force of gravity may provide a good explanation for the observations. Key Points: There is a present‐day geophysical anomaly in the upper mantle co‐located with unusually young volcanism in the Central Appalachians We synthesize constraints from geophysics, petrology/geochemistry, and geomorphology to constrain possible models for lithospheric loss We favor one or more Rayleigh‐Taylor lithospheric instabilities, perhaps in combination with shear‐driven upwelling